THE ISLAMIC COMPOUNDING MECHANISMS FOR SUSTAINABLE DEVELOPMENT GOALS AND GREEN FINANCIAL INNOVATION - Ahmad Azim Aufaq; Andriani Samsuri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the compatibility of compounding theory with Islamic investment principles in promoting business sustainability, green transition, and the achievement of the Sustainable Development Goals (SDGs). Using a qualitative-descriptive method and normative legal analysis, it finds that an Islamic Compounding Mechanism (ICM) based on the Base Profit Rate (BPR) can support exponential wealth accumulation without violating core shariah principles, provided it is structured through permissible contracts such as murabaha, musharaka, and mudharaba. The study further highlights that this mechanism can align profit growth with sustainable business practices and environmentally responsible investment. It thus proposes ICM as a practical framework for integrating shariah compliance, ethical wealth creation, and sustainability objectives in contemporary Islamic finance.